Preparation method of multidimensional porous niobium oxide film

By preparing niobium oxide films using anodized method using ammonium fluoride, glycerol or dipotassium hydrogen phosphate, the problem of morphology control of Nb2O5 materials in the prior art was solved, and porous oxidation with high activity, high specific surface area and stability was achieved. Niobium films improve their performance in the fields of electrochemical and photoelectric conversion.

CN119194557APending Publication Date: 2024-12-27GUANGDONG LABORATORY OF CHEMISTRY & FINE CHEMICAL IND JIEYANG CENTER JIEYANG +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411114355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

It is difficult to prepare nanoscale Nb2O5 materials with regular morphology, high activity, high specific surface area and high stability, especially because their chemical inertia is not conducive to kinetic controlled crystal growth.

Method used

Ammonium fluoride, glycerol or dipotassium hydrogen phosphate and glycerol as electrolytes, niobium oxide film is generated by anodizing method, and porous niobium oxide film is obtained by roasting, and the pore size and wall thickness are controlled to be nanoscale to achieve high Activity and stability.

Benefits of technology

The prepared porous niobium oxide film has a high specific surface area and a multi-dimensional pore structure, which improves electrochemical performance and photoelectric conversion efficiency, and is suitable for electrode materials and solar energy applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194557A_ABST
    Figure CN119194557A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multidimensional porous niobium oxide film, and relates to the technical field of metal oxides. The preparation method comprises the following steps: placing a niobium sheet in an electrolyte, and obtaining an amorphous niobium oxide film through an anodic oxidation method; roasting the amorphous niobium oxide film to obtain a porous niobium oxide film; the electrolyte is a glycerol solution of ammonium fluoride and / or a glycerol solution of dipotassium phosphate; the electrolyte does not contain water. The niobium oxide thin film is a semiconductor photo-anode material, is not easy to fall off from a substrate niobium sheet, has good stability, regular morphology, a specific crystal structure, a wide potential window and stable chemical performance, can be used for preparing an electrode material, can improve the electrical performance of a battery or a hybrid capacitor, and has wide application prospects. And the application of solar energy in photoelectric conversion is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal oxides, and in particular to a method for preparing a multi-dimensional porous niobium oxide film. Background Art

[0002] Solar energy has attracted much attention as a clean energy that can replace fossil energy. At present, the development and utilization of solar energy mainly include photothermal conversion, photoelectric conversion and photochemical conversion. The combination of solar energy and semiconductor photoanode can realize photoelectric conversion, such as photocatalysis and photoelectrocatalysis technology, and can also be applied in the field of photocatalytic degradation of organic pollutants and photocatalytic oxygen production, thereby solving the energy and environmental problems faced by social development. The key to realizing the application of solar energy in photoelectric and photocatalytic applications is to find suitable semiconductor photoanode materials.

[0003] At present, the semiconductor photoanode materials reported include TiO2, Nb2O5, ZnO, CdS, Ta2O5, etc. Among them, Nb2O5 is a new type of wide bandgap semiconductor material as a photoanode material, which has the advantages of high conduction band edge, good chemical stability, low price, non-toxic and pollution-free, etc. It shows excellent performance in electrochemistry, electrochromic devices, ultraviolet photodetectors, catalysts and dye-sensitized solar cells, and is widely used in the fields of electronics, ceramic materials, photocatalysis, optical glass and aerospace industry. As the application fields are increasingly pursuing the characteristics of their products and becoming more specialized, the requirements for the quality and physical properties of Nb2O5 in various industries are getting higher and higher. For example, in energy devices such as solar cells, rechargeable batteries and supercapacitors, Nb2O5 is required to have the characteristics of high energy storage; in terms of being a photocatalyst for treating organic pollutants in water, semiconductor Nb2O5 is required to have better optical properties to broaden the absorption wavelength range. At the same time, Nb2O5 can also be used as material electrodes for lithium batteries and hybrid capacitors, and Nb2O5 is required to have a large surface ion transport or charge transfer area.

[0004] By controlling the morphological characteristics of Nb2O5, such as pore size and specific surface area, the active sites can be increased and its electrochemical performance can be improved, thereby meeting the needs of more application fields. However, since Nb2O5 is chemically inert and relatively stable in nature, it is not conducive to kinetically controlled crystal growth, which makes it difficult to prepare Nb2O5 products with regular morphology, especially nanoscale Nb2O5 materials, with existing technologies. Therefore, finding a simple and fast route to diversify Nb2O5 crystal materials and prepare Nb2O5 materials with regular morphology, pore size and wall thickness that are highly active, high specific surface area and high stability will help further expand the depth and breadth of Nb2O5 applications. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a method for preparing a niobium oxide thin film, using ammonium fluoride and glycerol, or dipotassium hydrogen phosphate and glycerol as an electrolyte, and obtaining niobium oxide by an anodic oxidation method, wherein the niobium oxide material has a regular morphology and multi-dimensional pores, and achieves high activity, high specific surface area and high stability.

[0006] A second aspect of the present invention is to provide a niobium oxide thin film.

[0007] The third aspect of the present invention is to provide an application of a niobium oxide film.

[0008] A fourth aspect of the present invention is to provide an electrode material.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A first aspect of the present invention provides a method for preparing a porous niobium oxide film, comprising the following steps:

[0011] The niobium sheet is placed in an electrolyte to form an amorphous niobium oxide film by an anodic oxidation method;

[0012] calcining the amorphous niobium oxide film to obtain a porous niobium oxide film;

[0013] The electrolyte is a glycerol solution of ammonium fluoride and / or a glycerol solution of dipotassium hydrogen phosphate; and the electrolyte does not contain water.

[0014] The present invention uses glycerol as a solution to prepare an electrolyte. Glycerol helps to form a uniform and dense oxide film. On the other hand, the molecular structure of glycerol enables it to interact well with the surface of the niobium sheet, thereby promoting the formation of a niobium oxide film. At the same time, glycerol can control the reaction rate and the thickness of the niobium oxide film during the anodic oxidation process, and has good control over the reaction rate and the thickness of the oxide film. In addition, glycerol also has good electrolyte properties, helps to provide necessary ion transmission, and maintains the stability of the electrolyte, thereby promoting the anodic oxidation reaction.

[0015] In addition, the electrolyte used in the present invention does not contain water, which can avoid the appearance of mottled film surface or the phenomenon of the electrolyte being burnt, and can increase the pore size and stability of the niobium oxide film.

[0016] In some embodiments of the present invention, the voltage of the anodization is 20-60V.

[0017] In some embodiments of the present invention, the voltage of the anodization is 20-30V.

[0018] In some specific embodiments of the present invention, the voltage of the anodization is 20-25V.

[0019] In some examples of the present invention, when the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, the anode oxidation voltage is 20-22V.

[0020] In some embodiments of the present invention, when the electrolyte is a glycerol solution of ammonium fluoride, the oxidation time of the anodic oxidation is 2 to 4 hours.

[0021] In some embodiments of the present invention, when the electrolyte is a glycerol solution of ammonium fluoride, the oxidation time of the anodic oxidation is 3 to 4 hours.

[0022] In some embodiments of the present invention, when the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, the time of the anodic oxidation is 10 to 20 minutes.

[0023] In some embodiments of the present invention, when the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, the time of the anodization is 16 to 17 minutes.

[0024] In some embodiments of the present invention, the electrolyte is a glycerol solution of ammonium fluoride, and the concentration of ammonium fluoride in the electrolyte is 0.4-1.2 mol / L.

[0025] In some embodiments of the present invention, the electrolyte is a glycerol solution of ammonium fluoride, and the concentration of ammonium fluoride in the electrolyte is 0.8-1.2 mol / L.

[0026] In some embodiments of the present invention, the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, and the mass concentration of dipotassium hydrogen phosphate in the electrolyte is 8-12%.

[0027] In some embodiments of the present invention, the number of times of anodization is 1 to 2 times.

[0028] In some embodiments of the present invention, when the anodizing is performed for the second time, the amorphous niobium oxide film generated by the first anodizing is first removed.

[0029] In some embodiments of the present invention, the calcination temperature is 450-650°C.

[0030] In some embodiments of the present invention, the calcination temperature is 500-550°C.

[0031] In some embodiments of the present invention, the anodic oxidation method uses a platinum sheet as a cathode and the niobium sheet as an anode.

[0032] The platinum sheet is connected to the cathode of the power supply, and the niobium sheet is connected to the anode of the power supply, and a layer of niobium oxide film is generated on the surface of the niobium sheet by anodization.

[0033] In some embodiments of the present invention, the anodizing method is performed by an anodizing device; the anodizing device comprises an electrolytic cell, a direct current power supply, a platinum sheet, a niobium sheet and a conductive layer.

[0034] In some embodiments of the present invention, after the anodizing, a washing step is further included; the washing is rinsing or ultrasound.

[0035] In some embodiments of the present invention, the solution used for washing is anhydrous ethanol.

[0036] The second aspect of the present invention provides a porous niobium oxide film obtained by the preparation method described in the first aspect of the present invention, wherein the maximum pore size of the porous niobium oxide film is 150 nm.

[0037] The porous niobium oxide film obtained by the preparation method provided by the first aspect of the present invention has a nanostructured film with multidimensional pores and a large pore size. The larger pore size is conducive to providing a larger surface area, increasing the active sites of electrochemical reactions, and promoting charge transfer and rapid ion transport. In addition, the large pore size can reduce the mass transfer resistance, form a wide channel, allow ions or molecules to pass more easily, and help improve the rate performance of the device; at the same time, the larger pore size of the porous niobium oxide film can also enhance the electrochemical performance, increase the specific surface area of ​​the capacitor material, improve the capacitance and rapid charge and discharge capabilities, reduce expansion stress, and improve cycle stability. Therefore, the multidimensional pore structure with a large pore size is conducive to improving the ion transport and charge transfer efficiency of the porous niobium oxide film and improving its electrochemical performance.

[0038] Among them, multi-dimensional pore structure refers to a porous structure with multi-scale, multi-directional and multi-level characteristics, with pore distribution ranging from nanometer to micrometer, forming a complex three-dimensional network. These pores can be highly ordered and evenly distributed, or a combination of mesopores, micropores and macropores, providing an open transmission path.

[0039] In some embodiments of the present invention, the maximum pore size of the porous niobium oxide film is 100 nm±2%, and the minimum pore size is 10 nm±2%.

[0040] In some embodiments of the present invention, the pore size distribution of the porous niobium oxide film is 10-100 nm.

[0041] In some embodiments of the present invention, the pore size distribution of the porous niobium oxide film is 10-70 nm.

[0042] In some embodiments of the present invention, the average pore size of the porous niobium oxide film is 10 to 50 nm.

[0043] In some embodiments of the present invention, the specific surface area of ​​the porous niobium oxide film is 100 to 150 m 2 / g.

[0044] In some embodiments of the present invention, the specific surface area of ​​the porous niobium oxide film is 140-150 m 2 / g.

[0045] In some embodiments of the present invention, the thickness of the porous niobium oxide film is 1 to 5 nm.

[0046] In some embodiments of the present invention, the thickness of the porous niobium oxide film is 2-4 nm.

[0047] In some embodiments of the present invention, the pore wall thickness of the porous niobium oxide film is 9-11 nm.

[0048] The third aspect of the present invention provides a porous niobium oxide film obtained by the preparation method described in the first aspect of the present invention, or use of the porous niobium oxide film described in the second aspect of the present invention in preparing electrode materials.

[0049] The fourth aspect of the present invention is to provide an electrode material, comprising the porous niobium oxide film obtained by the preparation method described in the first aspect of the present invention, or the porous niobium oxide film described in the second aspect of the present invention.

[0050] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0051] (1) The preparation method of the present invention is simple and the required equipment is simple. The obtained porous niobium oxide film is a nanostructured film, which is tightly bonded to the base electrode (i.e., niobium sheet), is not easy to fall off the base niobium sheet, has good stability, has quantum size effect and orientation effect, and can improve the photoelectric conversion efficiency; the porous niobium oxide film has a highly ordered crystal structure array, regular morphology, multi-dimensional pores, large pore size, and has significant advantages in surface ion transport and charge transfer, and has a wide potential window and stable chemical properties; the obtained niobium oxide film nanostructure is continuously distributed and tightly arranged, grows vertically to the surface of the niobium sheet, and has a high specific surface area of ​​150 m 2 / g, with more active sites, the adsorption performance, light absorption, photoelectric conversion efficiency and other properties have been improved.

[0052] (2) The present invention can better control the pore size and thickness of the niobium oxide film by further improving the conditions of anodization, and further adjusting the calcination temperature is conducive to controlling the crystal form of niobium oxide. Under appropriate anodization conditions, a niobium oxide nanostructure with better morphology and nanometer-scale pore size and wall thickness can be formed.

[0053] (3) The niobium oxide film of the present invention is a semiconductor photoanode material, which is not easy to fall off from the base niobium sheet, has good stability, regular morphology, a specific crystal structure, a wide potential window and stable chemical properties, can be used to prepare electrode materials, can improve the electrical properties of batteries or hybrid capacitors, and realize the application of solar energy in photoelectric conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 A diagram of an anodizing device used in embodiments and comparative examples of the present invention.

[0055] Figure 2 The SEM images of the niobium oxide films obtained in Examples 1 to 3 of the present invention are shown in FIG. Figure 2 (a) to (c) correspond to the SEM images of the niobium oxide thin films of Examples 1 to 3, respectively.

[0056] Figure 3 The SEM images of the niobium oxide films obtained in Examples 4 to 7 of the present invention are shown in FIG. Figure 3 (a)~(b), Figure 3 (c)~(d), Figure 3 (e)~(f) Figure 3 (g) to (h) correspond to the SEM images of the niobium oxide thin films of Example 4, Example 5, Example 6, and Example 7, respectively.

[0057] Figure 4 The SEM images of the niobium oxide films obtained in Examples 8 to 10 of the present invention are as follows; Figure 4 (a)~(b), Figure 4 (c)~(d), Figure 4 (e) to (f) correspond to the SEM images of the niobium oxide thin films of Example 8, Example 9, and Example 10, respectively.

[0058] Figure 5 The SEM images of the niobium oxide films obtained in Examples 11 to 14 of the present invention are as follows; Figure 5 (g)~(h), Figure 5 (i)~(j), Figure 5 (k)~(l), Figure 5 (m) to (n) correspond to the SEM images of the niobium oxide thin films of Example 11, Example 12, Example 13, and Example 14, respectively.

[0059] Figure 6 The SEM images of the niobium oxide films obtained in Examples 15 to 17 of the present invention are as follows; Figure 6 (a)~(b), Figure 6 (c)~(d), Figure 6(e) to (g) correspond to the SEM images of the niobium oxide thin films of Example 15, Example 16, and Example 17, respectively.

[0060] Figure 7 The SEM images of the niobium oxide films obtained in Examples 18 to 20 of the present invention are as follows; Figure 7 (a)~(c) Figure 7 (d)~(e), Figure 7 (f) to (h) correspond to the SEM images of the niobium oxide thin films of Example 18, Example 19, and Example 20, respectively.

[0061] Figure 8 The SEM images of the niobium oxide films obtained in Comparative Examples 2 to 3 of the present invention are shown in FIG. Figure 8 (a)~(b), Figure 8 (c) to (d) correspond to the SEM images of the niobium oxide thin films of Comparative Example 2 and Comparative Example 3, respectively.

[0062] right Figure 1 The annotations are as follows:

[0063] 100-electrolytic cell, 200-DC power supply, 300-platinum sheet, 400-niobium sheet, 500-conductive layer. DETAILED DESCRIPTION

[0064] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0065] The niobium sheets used in the following embodiments of the present invention are pretreated, and the pretreatment steps are as follows:

[0066] The pure niobium sheet was cut into small pieces of 1.5×1.5 cm, and ultrasonicated in acetone, methanol, and deionized water for 15 min in turn to remove grease and impurities on the surface. Then, it was chemically polished in a mixture of HF / HNO3 / H2O (volume ratio of 1:4:5) for 10 min to obtain a smooth surface, and then dried with nitrogen for later use.

[0067] The preparation method of the glycerol solution of ammonium fluoride used in the following embodiments of the present invention is as follows:

[0068] Since glycerol is viscous and easy to stick to the wall, it may cause a large error in the measured volume. Therefore, it is necessary to convert the mass of the weighed glycerol before preparing it. For example, if you need to prepare 50ml of ammonium fluoride glycerol solution, the density of glycerol at room temperature is 1.261g / cm 3, the mass of glycerol required is calculated to be 63.05g;

[0069] Since ammonium fluoride is not easily soluble in glycerol, the ammonium fluoride is first ground for 20 minutes and then poured into the glycerol solution, a stirring bar is added, and the mixture is placed on a magnetic stirrer. The mixture is stirred at 80°C and 200 r / min for 4 hours until the ammonium fluoride is completely dissolved in the glycerol to obtain a glycerol solution of ammonium fluoride without water, which is then cooled to room temperature for later use.

[0070] The masses of ammonium fluoride and glycerol used to prepare glycerol solutions of ammonium fluoride of different concentrations are shown in Table 1:

[0071] Table 1 The mass of ammonium fluoride and glycerol required to prepare ammonium fluoride glycerol solutions with different ammonium fluoride concentrations

[0072] Concentration (mol / L) Mass of ammonium fluoride (g) Glycerol mass (g) 0.4 0.7480 63.0500 0.8 1.4960 63.0500 1.2 2.2440 63.0500

[0073] The preparation method of the glycerol solution of dipotassium hydrogen phosphate used in the following examples of the present invention is as follows:

[0074] Weigh 63.0500 g of glycerol and 7.0000 g of anhydrous dipotassium hydrogen phosphate, add the anhydrous dipotassium hydrogen phosphate to the glycerol solution, add a stirrer, heat to 180°C on a magnetic heating stirrer, maintain at 200 r / min for 4 hours to reduce the water content, and prepare 50 mL of a 10% mass fraction of dipotassium hydrogen phosphate in glycerol anhydrous solution.

[0075] The following is a detailed description with reference to different embodiments:

[0076] Example 1

[0077] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, comprising the following steps:

[0078] The pretreated niobium sheet is placed in an electrolyte and an amorphous niobium oxide film is obtained by an anodic oxidation method; the electrolyte is a glycerol solution of ammonium fluoride, and the concentration of ammonium fluoride in the electrolyte is 0.4 mol / L; the apparatus used in the anodizing method is as follows Figure 1 As shown, a niobium sheet 400 is fixed in an electrolytic cell 100, the niobium sheet 400 is connected to the anode of a DC power supply 200, the platinum sheet 300 is connected to the cathode of the DC power supply 200, and the vertical distance between the niobium sheet 400 and the platinum sheet 300 is adjusted to 1 cm; the voltage of the DC power supply 200 is first adjusted to the voltage required for anodization 20V under no-load conditions, the power supply is turned on, the voltage is maintained at 20V, anodization is performed for 2 hours, and the power supply is turned off;

[0079] The function of the conductive layer 500 is to make the porous niobium oxide film grow more uniformly and the electron transmission more uniform;

[0080] After anodization, an amorphous niobium oxide film is formed on the surface of the niobium sheet. The niobium sheet is removed and rinsed with anhydrous ethanol for 3 to 5 minutes and then blown dry with nitrogen.

[0081] The niobium sheet containing the amorphous niobium oxide film was calcined under air conditions at a gas flow rate of 50 mL / min and a temperature increase of 5° C. / min to 550° C. for 2 hours to obtain a porous niobium oxide film.

[0082] Example 2

[0083] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 1 in that the voltage of the anodization is 25V.

[0084] Example 3

[0085] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 1 in that the voltage of the anodic oxidation is 30V.

[0086] Example 4

[0087] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 1 in that the concentration of ammonium fluoride in the electrolyte is 0.8 mol / L.

[0088] Example 5

[0089] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 4 in that the anodic oxidation voltage is 25V.

[0090] Example 6

[0091] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 4 in that the anodic oxidation voltage is 30V.

[0092] Example 7

[0093] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 4 in that the anodizing time is 3 hours.

[0094] Example 8

[0095] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 1 in that the concentration of ammonium fluoride in the electrolyte is 1.2 mol / L.

[0096] Example 9

[0097] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 8 in that the anodic oxidation voltage is 25V.

[0098] Example 10

[0099] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 8 in that the anodic oxidation voltage is 30V.

[0100] Embodiment 11

[0101] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 8 in that the anodizing time is 3 hours.

[0102] Example 12

[0103] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 11 in that the anodizing voltage is 25V.

[0104] Example 13

[0105] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from Embodiment 11 in that the anodizing voltage is 30V.

[0106] Embodiment 14

[0107] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which differs from Embodiment 13 in that the anodizing time is 4 hours.

[0108] Embodiment 15

[0109] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film. The difference from Embodiment 5 is that this embodiment performs two anodizations, and the second anodization specifically includes the following steps:

[0110] The niobium sheet after anodization in Example 5 was ultrasonically placed in deionized water for 30 minutes to remove the amorphous niobium oxide film generated by the first anodization, and then dried with nitrogen. The niobium sheet was anodized for the second time (25V, 2h) with the same parameters as Example 5, washed, and calcined to obtain a niobium oxide film.

[0111] Example 16

[0112] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which differs from Embodiment 15 in that the parameters of the second anodization are: the concentration of ammonium fluoride in the electrolyte is 1.2 mol / L, the anodization voltage is 30 V, and the anodization time is 3 h.

[0113] Embodiment 17

[0114] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which differs from Embodiment 15 in that the parameters of the second anodization are: the concentration of ammonium fluoride in the electrolyte is 1.2 mol / L, the anodization voltage is 30 V, and the anodization time is 4 h.

[0115] Embodiment 18

[0116] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, comprising the following steps:

[0117] The pretreated niobium sheet is placed in an electrolyte to obtain an amorphous niobium oxide film by anodization; the electrolyte is a 10% by mass solution of potassium dihydrogen phosphate in glycerol; the apparatus used in the anodization method is the same as in Example 1, and the target area of ​​anodization is set to 1×1 cm on one side of the niobium sheet, and the unnecessary part is wrapped with raw tape for protection. The device is connected to a DC power supply 200, such as Figure 1 As shown, the niobium sheet 400 is connected to the anode of the power supply 200, and the platinum sheet 300 is connected to the cathode of the power supply 200. The vertical distance between the niobium sheet 400 and the platinum sheet 300 is adjusted to 1 cm. During the anodizing process, the electrolyte temperature is maintained at 180°C and the speed is maintained at 200r / min. The electrolyte can just cover the niobium sheet and cannot be connected to the metal clip. The anodizing voltage is set to 20V, and the anodizing time is 15min.

[0118] After anodization, an amorphous niobium oxide film is formed on the surface of the niobium sheet. The niobium sheet is removed and rinsed with deionized water and soaked for 10 minutes, and then dried naturally in the air.

[0119] The niobium sheet containing the amorphous niobium oxide film was calcined under air conditions with a gas flow rate of 50 mL / min and a temperature increased at 5° C. / min to 550° C. for 2 hours to obtain a niobium oxide film.

[0120] Embodiment 19

[0121] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which differs from Embodiment 18 in that the anodizing voltage is 25V.

[0122] Embodiment 20

[0123] This embodiment provides a method for preparing a multi-dimensional porous niobium oxide film, which differs from Embodiment 18 in that the anodizing time is 20 minutes.

[0124] Comparative Example 1

[0125] This comparative example provides a method for preparing a multidimensional porous niobium oxide film, which is different from Example 1 in that: a glycerol solution containing aqueous ammonium fluoride is used as an electrolyte, the water content in the electrolyte is 0.5 mol / L, the concentration of ammonium fluoride is 1.2 mol / L, and the ammonium fluoride is dissolved in glycerol under stirring at 80° C. and 200 r / min for 4 hours;

[0126] The difference between the anodizing process and Example 1 is that the anodizing voltage is 40 V and the anodizing time is 1 h.

[0127] Comparative Example 2

[0128] This comparative example provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from comparative example 1 in that the anodic oxidation voltage is 50V.

[0129] Comparative Example 3

[0130] This comparative example provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from comparative example 1 in that the anodic oxidation voltage is 60V.

[0131] Comparative Example 4

[0132] This comparative example provides a method for preparing a multi-dimensional porous niobium oxide film, which is different from comparative example 1 in that the anodic oxidation voltage is 90V.

[0133] Results

[0134] The niobium oxide films obtained in the above examples and comparative examples were characterized. Figures 2 to 8 As shown:

[0135] Figure 2 The SEM images of the niobium oxide films obtained in Examples 1 to 3 of the present invention are shown in FIG. Figure 2 (a) to (c) are SEM images of niobium oxide thin films of Examples 1 to 3, respectively. The pore size of the film obtained in the electrolyte of 0.4 mol / L ammonium fluoride glycerol solution is small, and crystals are attached to the surface of the film, which may be due to the fact that the ammonium fluoride crystals have not been washed away. Figure 2 (a) to (c) show that, under the same conditions, as the voltage increases, the niobium oxide film becomes denser and more regular, and the film thickness increases. However, the greater the voltage, the less "solid" the generated niobium oxide film is, the easier it is to fall off, and the poorer the stability. When the oxidation voltage is 25 to 30 V, better results can be obtained.

[0136] Figure 3 The SEM images of the niobium oxide films obtained in Examples 4 to 7 of the present invention are shown in FIG. Figure 3 (a)~(b), Figure 3 (c)~(d), Figure 3(e)~(f) Figure 3 (g) to (h) are SEM images of the niobium oxide thin films of Example 4, Example 5, Example 6, and Example 7, respectively. The pore size of the niobium oxide thin film obtained in the electrolyte of 0.8 mol / L ammonium fluoride glycerol solution is about 20 nm larger than that of the 0.4 mol / L solution. Figure 3 (a) to (f) it can be seen that when the voltage gradually increases, the peeling phenomenon of the niobium oxide film becomes more serious, the pore size increases slightly, and the thickness of the niobium oxide film increases; Figure 3 (a) to (b) and Figure 3 (g) to (h) show that the longer the oxidation time, the larger the pore size. This is because as the oxidation time increases, the more serious the corrosion of the surface of the niobium oxide film. After the pore corrosion, the pores are interconnected to form gullies, which makes the pore size larger. At the same time, when the surface is fully corroded, the larger pores under the niobium oxide film will be exposed. Under the conditions of the same concentration and the same voltage, the longer the oxidation time, the more serious the surface corrosion and the larger the film pore size. The oxidation time is the key factor affecting the pore size. In the present invention, the optimal oxidation time is 4h.

[0137] Figure 4 The SEM images of the niobium oxide films obtained in Examples 8 to 10 of the present invention are as follows; Figure 4 (a)~(b), Figure 4 (c)~(d), Figure 4 (e) to (f) correspond to the SEM images of the niobium oxide thin films of Example 8, Example 9, and Example 10, respectively. Figure 5 The SEM images of the niobium oxide films obtained in Examples 11 to 14 of the present invention are as follows; Figure 5 (g)~(h), Figure 5 (i)~(j), Figure 5 (k)~(l), Figure 5 (m) to (n) correspond to the SEM images of the niobium oxide thin films of Example 11, Example 12, Example 13, and Example 14, respectively. The pore size of the niobium oxide thin film obtained in the electrolyte of 1.2 mol / L ammonium fluoride glycerol solution is larger than that of 0.4 mol / L and 0.8 mol / L. Figure 4 (a) to (f) and Figure 5 As can be seen from (g) to (l), when other conditions are the same, the voltage gradually increases, and the thickness of the niobium oxide film increases significantly, but at the same time the film is more easily damaged, and a small amount of nanotubes are generated at a voltage of 30V. Figure 4 (a) to (f) and Figure 5 (g) to (n), it can be seen that the longer the oxidation time, the more serious the corrosion of the niobium oxide film surface, the larger the pore size, and the Figure 2 and Figure 3By comparison, it can be seen that the greater the concentration of ammonium fluoride in the electrolyte, the larger the pore size of the obtained niobium oxide film. When the concentration of ammonium fluoride is 0.4 mol / L, the average pore size is 10 nm and the maximum pore size is 30 nm; when the concentration of ammonium fluoride is 1.2 mol / L, the average pore size is 50 nm and the maximum pore size is 70 nm; the film thickness increases, the thickness is 2 nm when the concentration of ammonium fluoride is 0.4 mol / L, and the thickness is 4 nm when the concentration of ammonium fluoride is 1.2 mol / L, and the thickness of the growing film is faster. When the thickness of the film increases, the mechanical strength of the porous niobium oxide film is improved, the electrical conductivity is increased, the thermal conductivity is improved, and the energy storage capacity is enhanced. At the same time, the film can also provide better protection performance, increase light absorption efficiency, optimize electronic performance, and improve the stability and shielding ability of the film. However, when too much ammonium fluoride is added, the solution tends to be saturated and the ammonium fluoride cannot be completely dissolved.

[0138] Figure 6 The SEM images of the niobium oxide films obtained in Examples 15 to 17 of the present invention are as follows; Figure 6 (a)~(b), Figure 6 (c)~(d), Figure 6 (e) to (g) correspond to the SEM images of the niobium oxide thin films of Example 15, Example 16, and Example 17, respectively. Figure 6 (a) to (b) and Figure 3 Compare (c) to (d). Figure 6 (c)~(d) and Figure 5 Compared with (k) to (l), under the premise of maintaining a large pore size, the large pores continue to grow and interweave to form a network structure, which greatly increases the specific surface area. The BET test results show that the specific surface area reaches 150m 2 / g. Figure 6 (e)~(g) and Figure 5 Compared with (m) to (n), the film of the first anodized film has a larger pore size and a thinner thickness; the second anodized film thickens the pore wall thickness of the large pore size, not just the film thickness, and the pore size of the second anodized film is larger than that of the first anodized film, and some pores are opened to 100 to 200 nm. At the same time, due to the high concentration of the electrolyte, Figure 6 In (e), the electrolyte was found to be oversaturated and crystals were precipitated. Figure 6 (g) It was found that the lower layer of the secondary anodized substrate has a tendency to grow nanonodes, which is conducive to further research on niobium oxide nanotubes. It can be seen that secondary anodization can obtain a niobium oxide film with a large pore size, thin pore wall, and a large specific surface area.

[0139] Combination Figures 2 to 6It can be seen that in the anodic oxidation using ammonium fluoride glycerol solution as the electrolyte, the greater the concentration of ammonium fluoride, the larger the pore size of the niobium oxide film and the faster the film grows. For example, in Example 2 and Example 3, Example 9 and Example 10, the voltage is changed, and the pore size increase with a large concentration is smaller than the pore size increase with a small concentration. Under the conditions of the same concentration and the same oxidation time, the greater the voltage, the larger the pore size and the thicker the film, but the voltage is not the main reason for the increase in pore size. When the niobium oxide film becomes thicker, its vulnerability is greatly increased, and it is not firm and has poor stability. Under the conditions of the same concentration and the same voltage, the longer the oxidation time, the more serious the surface corrosion of the niobium sheet, and the larger the pore size of the niobium oxide film. The oxidation time is the most important factor affecting the pore size. On the one hand, the surface corrosion pores, the pores are connected to each other to form gullies, which increase the pores. On the other hand, when the surface corrosion of the niobium oxide film is more serious, the upper pores have been completely corroded, exposing the channels with larger pores in the lower layer, and the maximum pore size reaches about 100nm. In addition, water in the electrolyte is not conducive to the formation of niobium oxide film. The surface of the obtained niobium sheet is easily burnt and blocks the pores of the film, and the film is easy to separate from the niobium sheet substrate.

[0140] Figure 7 The SEM images of the niobium oxide films obtained in Examples 18 to 20 of the present invention are as follows; Figure 7 (a)~(c) Figure 7 (d)~(e), Figure 7 (f) to (h) are SEM images of the niobium oxide thin films of Example 18, Example 19, and Example 20, respectively. It can be seen that when the oxidation time of Example 18 and Example 19 is the same, the voltage increases, the surface of the obtained niobium oxide thin film is irregular, and the film thickness increases; when the oxidation time of Example 18 and Example 20 is changed, there is almost no effect on the pore size. It can be seen that when the solute in glycerol is dipotassium hydrogen phosphate, the oxidation time has little effect on the pore size of the obtained niobium oxide thin film.

[0141] Using a propylene glycol solution of dipotassium hydrogen phosphate as the electrolyte makes the operation simpler and saves more time. The resulting niobium oxide film is similar to a plated film, firmly adheres to the niobium sheet substrate, and has better stability.

[0142] Figure 8 The SEM images of the niobium oxide films obtained in Comparative Examples 2 to 3 of the present invention are shown in FIG. Figure 8 (a)~(b), Figure 8(c) to (d) correspond to the SEM images of the niobium oxide thin films of Comparative Examples 2 and 3, respectively. The present invention found that in Comparative Example 1, when the propylene glycol solution containing ammonium fluoride was used as the electrolyte, the film began to grow only when the voltage reached 40V, and the niobium oxide thin film grew completely at 50V. At 60V or above, the film surface began to have yellow spots, and the electrolyte showed signs of burning. Compared with the niobium oxide thin film obtained by anodizing with an anhydrous electrolyte in the embodiment, the pores were uneven, the film was peeling, the pore size was too small, the film thickness was thin, and there were obvious signs of blocked pores on the film base. Therefore, the presence of water in the electrolyte is not conducive to the formation of niobium oxide thin film by anodization, and it also affects the firmness of the film. The obtained niobium oxide thin film is easy to separate from the niobium metal sheet and has poor stability.

[0143] In summary, the preparation method of the present invention is simple, the required equipment is simple, and the obtained niobium oxide film is a nanostructured film, which is tightly combined with the base electrode (i.e., niobium sheet) and has good stability. The porous niobium oxide film of the present invention has a nanostructure, possesses quantum size effect and orientation effect, and can improve the photoelectric conversion efficiency; the niobium oxide film crystal structure array is highly ordered, the morphology is regular, and it has multidimensional channels and large pore size; it has a wide potential window and stable chemical properties; the nanostructure is continuously distributed and closely arranged, and grows perpendicular to the surface of the niobium sheet, with a high specific surface area, and the adsorption performance, light absorption, photoelectric conversion efficiency and other properties are all improved. The niobium oxide film can be used to prepare electrode materials, improve the electrical properties of batteries or hybrid capacitors, and realize the application of solar energy in photoelectric conversion.

[0144] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a porous niobium oxide film, characterized in that: The steps include: The niobium sheet is placed in an electrolyte and an amorphous niobium oxide film is obtained by an anodic oxidation method; calcining the amorphous niobium oxide film to obtain a porous niobium oxide film; The electrolyte is a glycerol solution of ammonium fluoride and / or a glycerol solution of dipotassium hydrogen phosphate; and the electrolyte does not contain water.

2. The preparation method according to claim 1, characterized in that: The voltage of the anodic oxidation is 20-60V.

3. The preparation method according to claim 1, characterized in that: When the electrolyte is a glycerol solution of ammonium fluoride, the oxidation time of the anodic oxidation is 2 to 4 hours; when the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, the oxidation time of the anodic oxidation is 10 to 20 minutes.

4. The preparation method according to claim 1, characterized in that: The electrolyte is a glycerol solution of ammonium fluoride, and the concentration of ammonium fluoride in the electrolyte is 0.4-1.2 mol / L; And / or, the electrolyte is a glycerol solution of dipotassium hydrogen phosphate, and the mass concentration of dipotassium hydrogen phosphate in the electrolyte is 8-12%.

5. The preparation method according to claim 1, characterized in that: The number of times of the anodization is 1 to 2 times.

6. The preparation method according to claim 1, characterized in that: The calcination temperature is 450-650°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The anodic oxidation method uses a platinum sheet as a cathode and the niobium sheet as an anode; And / or, after the anodizing, a washing step is also included; the washing is flushing or ultrasound.

8. A porous niobium oxide film obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The maximum pore size of the porous niobium oxide film is 150 nm.

9. Use of a porous niobium oxide film obtained by the preparation method according to any one of claims 1 to 7, or a porous niobium oxide film according to claim 8 in the preparation of electrode materials.

10. An electrode material, characterized in that: The porous niobium oxide film comprises the porous niobium oxide film obtained by the preparation method according to any one of claims 1 to 7, or the porous niobium oxide film according to claim 8.

Citation Information

Patent Citations

  • Preparation method of porous alloy electrocatalyst

    CN114032574A

  • Method for manufacturing porous niobium oxide by anodization

    KR1020130070395A

  • Method for anodizing valve metals

    US5837121A